Seasonal variability of coastal pH and CO2 using an oceanographic buoy in the Canary Islands - González González, Aridane; Aldrich-Rodríguez, Ariadna; González Santana, David; González Dávila, Melchor; Santana Casiano, Juana Magdalena (Frontiers in Marine Science, 2024)
Ocean acidification, caused by the absorption of carbon dioxide (CO2) from the atmosphere into the ocean, ranks among the most critical consequences of climate change for marine ecosystems. Most studies have examined pH and CO2 trends in the open ocean through oceanic time-series research. The analysis in coastal waters, particularly in island environments, remains relatively underexplored. This gap in our understanding is particularly important given the profound implications of these changes for coastal ecosystems and the blue economy. The present study focuses on the ongoing monitoring effort that started in March 2020 along the east coast of Gran Canaria, within the Gando Bay, by the CanOA-1 buoy. This monitoring initiative focuses on the systematic collection of multiple variables within the CO2 system, such as CO2 fugacity (fCO2), pH (in total scale, pHT), total inorganic carbon (CT), and other hydrographic variables including sea surface salinity (SSS), sea surface temperature (SST) and wind intensity and direction. Accordingly, the study allows the computation of the CO2 flux (FCO2) between the surface waters and the atmosphere. During the study period, stational (warm and cold periods) behavior was found for all the variables. The lowest SST values were recorded in March, with a range of 18.8-19.3°C, while the highest SST were observed in September and October, ranging from 24.5-24.8°C. SST exhibited an annual increase with a rate of 0.007°C yr-1. Warmer months increased SSS, while colder periods, influenced by extreme events like tropical storms, led to lower salinity (SSS=34.02). The predominant Trade Winds facilitated the arrival of deeper water, replenishing seawater. The study provided insights into atmospheric CO2. Atmospheric fCO2 averaged 415 ± 4 µatm (2020-2023). Surface water fCO2sw presented variability, with the highest values recorded in September and October, peaking at 437 µatm in September 2021. The lowest values for fCO2sw were found in February 2021 (368 µatm). From 2020 to 2023, ...